Software Piracy in Research: A Moral Analysis. - Santillanes, Gary; Felder, Ryan (Science & Engineering Ethics, 2015)
Researchers in virtually every discipline rely on sophisticated proprietary software for their work. However, some researchers are unable to afford the licenses and instead procure the software illegally. We discuss the prohibition of software piracy by intellectual property laws, and argue that the moral basis for the copyright law offers the possibility of cases where software piracy may be morally justified. The ethics codes that scientific institutions abide by are informed by a rule-consequentialist logic: by preserving personal rights to authored works, people able to do so will be incentivized to create. By showing that the law has this rule-consequentialist grounding, we suggest that scientists who blindly adopt their institutional ethics codes will commit themselves to accepting that software piracy could be morally justified, in some cases. We hope that this conclusion will spark debate over important tensions between ethics codes, copyright law, and the underlying moral basis for these regulations. We conclude by offering practical solutions (other than piracy) for researchers.